Group dynamics and argument mapping in university students’ dialogical argumentation - Tuzinkievicz, Maria Agustina (2025)
This study investigates how argument diagrams and group size affect argumentative interactions among university students completing academic tasks. Argumentation, essential in educational psychology, helps resolve sociocognitive conflicts through critical engagement and verbal interaction. The quasi-experimental design involved 100 first-year Psychology and Psychopedagogy students, some of whom used an argument mapping tool. Data analysis revealed that mediation improved argument generation and integration but not co-construction or opposition. Non-mediated groups showed higher levels of co-construction and opposition. The findings suggest that visual tools enhance dialogical argumentation, although the study´s limitations include a small sample and lack of non-verbal data. Future research should explore these dynamics in diverse contexts.